Characterization of T-Cell Responses to SMX and SMX-NO in Co-Trimoxazole Hypersensitivity Patients Expressing HLA-B*13:01 - Pratoomwun, Jirawat; Thomson, Paul; Jaruthamsophon, Kanoot; Tiyasirichokchai, Rawiporn; Jinda, Pimonpan; Rerkpattanapipat, Ticha; Tassaneeyakul, Wichittra; Nakkam, Nontaya; Rerknimitr, Pawinee; Klaewsongkram, Jettanong; Srinoulprasert, Yuttana; Pirmohamed, Munir; et al. (Frontiers in Immunology, 2021)
HLA-B*13:01-positive patients in Thailand can develop frequent co-trimoxazole hypersensitivity reactions. This study aimed to characterize drug-specific T cells from three co-trimoxazole hypersensitive patients presenting with either Stevens-Johnson syndrome or drug reaction with eosinophilia and systemic symptoms. Two of the patients carried the HLA allele of interest, namely HLA-B*13:01. Sulfamethoxazole and nitroso sulfamethoxazole specific T cell clones were generated from T cell lines of co-trimoxazole hypersensitive HLA-B*13:01-positive patients. Clones were characterized for antigen specificity and cross-reactivity with structurally related compounds by measuring proliferation and cytokine release. Surface marker expression was characterized via flow cytometry. Mechanistic studies were conducted to assess pathways of T cell activation in response to antigen stimulation. Peripheral blood mononuclear cells from all patients were stimulated to proliferate and secrete IFN- with nitroso sulfamethoxazole. All sulfamethoxazole and nitroso sulfamethoxazole specific T cell clones expressed the CD4+ phenotype and strongly secreted IL-13 as well as IFN-, granzyme B and IL-22. No secretion of IL-17 was observed. A number of nitroso sulfamethoxazole-specific clones cross-reacted with nitroso dapsone but not sulfamethoxazole whereas sulfamethoxazole specific clones cross-reacted with nitroso sulfamethoxazole only. The nitroso sulfamethoxazole specific clones were activated in both antigen processing-dependent and -independent manner, while sulfamethoxazole activated T cell responses via direct HLA binding. Furthermore, activation of nitroso sulfamethoxazole-specific, but not sulfamethoxazole-specific, clones was blocked with glutathione. Sulfamethoxazole and nitroso sulfamethoxazole specific T cell clones from hypersensitive patients were CD4+ which suggests that HLA-B*13:01 is not directly involved in the iatrogenic disease observed in co-trimoxazole hypersensitivity patients.